2019
DOI: 10.4018/978-1-5225-7365-4.ch065
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Learning in and out of the K-12 Classroom

Abstract: Today there is widespread ownership of mobile technology, including mobile phones, tablets, Chromebooks, among school-aged youth. To wit, researchers report that nearly 70% of 8- to 18-year-olds own their own mobile device. In parallel with increased accessibility and usage, researchers in various fields of education have begun to explore how mobile technology can impact teaching and learning. In this chapter, the work of pioneering scholars in the area of emerging technology in K-12 education are discussed. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The developed world has invested in big data, Internet of Things, Artificial Intelligence, 5G and cloud-based technologies to sustain teaching and learning during the COVID-19 lockdown (Zhu & Li, 2020). Bedesem and Arner (2019) noted widespread ownership of smartphones and tablets among school-aged youth in developed countries. A European Union comprehensive survey revealed that 70 percent of educators in its bloc had acknowledged the critical role that education played through systematic integration of technology by over 90 percent of the teachers (Buda, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The developed world has invested in big data, Internet of Things, Artificial Intelligence, 5G and cloud-based technologies to sustain teaching and learning during the COVID-19 lockdown (Zhu & Li, 2020). Bedesem and Arner (2019) noted widespread ownership of smartphones and tablets among school-aged youth in developed countries. A European Union comprehensive survey revealed that 70 percent of educators in its bloc had acknowledged the critical role that education played through systematic integration of technology by over 90 percent of the teachers (Buda, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social networking sites (SNSs) allow students to form cooperative groups, take a more active part in their education, and function as resources for one another (Hung & Yuen, 2010). Students and educators use motor devices such as PDAs, cell phones, and portable tools a lot since they are easily accessible, have Internet browsers, and can send and receive emails and SMS (Csete, Wong, & Vogel, 2004). These gadgets have been used for online shopping, voice recording, voice memos, video transfers, chat messages, and audio files, among other things (Landau & Lubin, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a widespread ownership of mobile technology, including mobile/ smartphones, tablets, chromebooks, among school-aged youth (Bedesem & Arner, 2019). Mobile technologies, especially newer, portable handheld devices such as smartphones and tablets allow students to carry out various activities such as, listening to music, watching videos, using a GPS, taking (and editing) photos and videos, taking notes and playing games.…”
Section: Introductionmentioning
confidence: 99%